Mineralogy of the clay fraction of alfisols in two slope curvatures: IV - spatial correlation with physical properties - Camargo, Lívia Arantes [UNESP]; Marques Júnior, José [UNESP]; Pereira, Gener Tadeu [UNESP] (Sociedade Brasileira de Ciência do Solo, 2013)
A influência da mineralogia da fração argila nos atributos físicos do solo é reportada na literatura; porém, as relações espaciais entre esses atributos são escassas em se tratando de Argissolos. O objetivo deste trabalho foi avaliar a correlação espacial entre os minerais da fração argila e atributos físicos de um Argissolo de origem arenítica. Os atributos mineralógicos como diâmetro médio do cristal (DMC); largura à meia altura (LMA) dos minerais hematita, goethita, caulinita e gibbsita; teor; substituição isomórfica (SI); área de superfície específica (ASE) dos minerais hematita e goethita; razão goethita/(goethita+hematita); e razão caulinita/(caulinita+gibbsita) foram correlacionados com os atributos físicos por meio da correlação simples de Pearson e dos semivariogramas cruzados entre esses atributos. As relações encontradas entre a substituição isomórfica da goethita e os atributos físicos do solo permitiram inferir sobre o efeito da cristalinidade desse mineral nos atributos físicos do solo. Goethitas com altos valores de substituição isomórfica favoreceram a dimensão dos agregados e da porosidade; o contrário ocorreu com a densidade do solo (Ds) e resistência a penetração (RP). Gibbsitas de maior grau de cristalinidade favoreceram os maiores valores de densidade do solo e RP.

Although the influence of clay mineralogy on soil physical properties has been widely studied, spatial relationships between these features in Alfisols have rarely been examined. The purpose of this work was to relate the clay minerals and physical properties of an Alfisol of sandstone origin in two slope curvatures. The crystallographic properties such as mean crystallite size (MCS) and width at half height (WHH) of hematite, goethite, kaolinite and gibbsite; contents of hematite and goethite; aluminium substitution (AS) and specific surface area (SSA) of hematite and goethite; the goethite/(goethite+hematite) and kaolinite/(kaolinite+gibbsite) ratios; and the citrate/bicarbonate/dithionite extractable Fe (Fe d) were correlated with the soil physical properties through Pearson correlation coefficients and cross-semivariograms. The correlations found between aluminium substitution in goethite and the soil physical properties suggest that the degree of crystallinity of this mineral influences soil properties used as soil quality indicators. Thus, goethite with a high aluminium substitution resulted in large aggregate sizes and a high porosity, and also in a low bulk density and soil penetration resistance. The presence of highly crystalline gibbsite resulted in a high density and micropore content, as well as in smaller aggregates. Interpretation of the cross-semivariogram and classification of landscape compartments in terms of the spatial dependence pattern for the relief-dependent physical and mineralogical properties of the soil proved an effective supplementary method for assessing Pearson correlations between the soil physical and mineralogical properties.
Mineralogia da fração argila de um argissolo em curvaturas do relevo: II - correlação especial com atributos físicos
Keywords: aggregates; mineral crystallinity; Density; porosity; Penetration resistance; Cross semivariogram; Oxidos de ferro; Caulinita; Gibbsita; Densidade; agregados; semivariograma cruzado